45 Developing, evaluating, and implementing patient delivered intimate examination training across nine north-east london hospitals. (12th November 2018) - Duffy, JMN; Chequer, S; Braddy, A; Mylan, S; Royuela, A; Zamora, J; Ip, J; Hayden, S; Showell, M; Kinnersley, P; Chenoy, R; Westwood, OM; et al.
Abstract : Context: Pelvic examination is an essential component of the care women receive. Medical students are required to acquire these pelvic examination skills as a core competency. However, learning to perform the pelvic examination is difficult. Objective: We developed a novel patient delivered pelvic examination training intervention to improve educational outcomes. Strategy for improvement: Ninety-four medical students scheduled to undertake pelvic examination training were recruited into a randomised trial evaluating the educational effectiveness of patient-delivered training in the short and medium term. Results: During the clinical rotation, when compared with the control group, there was no difference in the number of examinations performed by participants in the experimental group. At the end of the clinical rotation, when compared with the control intervention, the experimental intervention had a moderate effect on knowledge [difference 29.9% (95% CI 11.2%–48.6%)] and participant confidence [difference 1 (95% CI 0–2)], and a large effect on participant comfort [difference 1.8 (95% CI 0.6–3.0)]. At the end of the academic year, the experimental intervention had a small effect on technical and interpersonal skills when compared with the control intervention. Median values were 24 (IQR 21–27) and 20 (IQR 17–24) in the experimental group compared with 24 (IQR 20–26) and 19 (IQR 17–22) in the control group, respectively. Lessons learnt: Among medical students taught the female pelvic examination by low-fidelity simulation, additional training by trained patients improved student, knowledge, comfort, and confidence at the end of the clinical rotation but did not improve examination skills at end of the academic year. Messages for others: Medical schools considering new or continuing investment in patient-delivered pelvic examination training should carefully consider its cost effectiveness, as it did not appear to produce any gains in summative assessments.